Gandhi- a Never Ending Inspiration: Reflection of Gandhian Thoughts in Mulk Raj Anand’s Untouchable and Raja Rao’s Kanthapura: Exploring Gandhian Thoughts in Indian English Literature (Journal of Advances and Scholarly Researches in Allied Education, 2019)
When we try to look back the world’s history, we may realize that the greatness of a man must be measured not by the amount of veneration accorded him but by the impact of his life on others. Around a century ago a leader was emerging who changed the course of a country’s struggle for independence. He inspired people from different caste, class, religion and language who become united to gain their freedom together. Mohandas Karamchand Gandhi, famously known as Mahatma Gandhi is a gift to the humanity in modern times, belongs to the line of great men who continued to influence every aspect of human life and tried to uplift them. He is a socio-political figure who is barely impossible for someone to forget or ignore.A writer’s work is sustained by the intellectual, religious, social,political and cultural milieu to which he belongs. From 1920 onwards Indian thoughts and life were greatly influenced by the powerful impact of the nationalist movement leads by Gandhi and Gandhian thoughts and philosophy. Indian English literature too was not left untouched with the popularity of Gandhi and his thoughts.Gandhian thought had a deep effect on the Indian writers especially on the Indo-Anglian writers. It helped them to connect with the contemporary society, the people and their problems like untouchability and caste system. Gandhi insisted on simple living and high thinking which was reflected and highlighted by the literary English authors of time in their novels, short-stories and poems. The Gandhian writers, presented Gandhi an important guest character or they presented a local Gandhi replica and presented him in the light of Mahatma and also as a god like Rama or Krishna. The great Indian English writers R.K. Narayan,Raja Rao, Mulk Raj Anand, and many other writersexplored Gandhian thoughts in their writings. Their novels follow Gandhian thoughts and his principles of Truth, Non-violence, Brotherhood, Satyagraha and his views on untouchability. This paper aims to explore the Gandhian thoughts and inspiration inMulk Raj Anand’s Untouchable and Raja Rao’s Kanthapura.